THE INFLUENCE OF THE KOREAN WAVE ON BEHAVIOR AMONG UIN AR-RANIRY BANDA ACEH STUDENTS - Sarah Dillah; Muhammad Thalal; Muhammad Yunus Ahmad (Indonesian Journal of Islamic History and Culture, 2022)
The Korean Wave refers to South Korean popular culture (pop culture), which has expanded throughout Asia, Europe, and America. This Korean Wave is being propagated through the entertainment sector, including music, movies, dramas, cosmetic goods, food, and so on, and is also being aided by the increasing flow of globalization. The goal of this study is to discover what variables impact the behavior of certain UIN Ar-Raniry students who like the Korean Wave and how the conduct of some UIN Ar-Raniry students who are influenced by the Korean Wave is affected. This study employed a qualitative method, with data collected through observation, interviews, and documentation. The acquired data was then examined using data analysis software. Data reduction, data presentation, conclusion drawing, and verification were used to examine the obtained data. The findings revealed that the effect of friends, families, and South Korean dramas presented on Indonesian private television channels influenced certain UIN Ar-Raniry students' liking of the Korean Wave. Some UIN Ar-Raniry students who were impacted by the Korean Wave may be noticed in their open conduct, use of language, style of dress, make-up and skin care, eating and food etiquette, and usage of social media. Their restricted conduct, methods of thinking and envisioning, growing knowledge or understanding, and developing self-confidence all have a shape.